A different perspective to the effective atomic number (Zeff) for some boron compounds and trommel sieve waste (TSW) with a new computer program ZXCOM - Yalcin, Zeynel; Icelli, Orhan; Okutan, Mustafa; Boncukcuoglu, Recep; Artun, Ozan; Orak, Salim (ELSEVIER, 2012)
In this study, the effective atomic number (Z(eff))has been calculated for some boron compounds, such as concentrate colemanite, tincal, ulexite, boric acid, probertite and TSW (Trommel Sieve Waste) by means of ZXCOM at incident beam energy (E-0=59.543 key) and scattering angle (theta=35 degrees). We present and discuss the (Z(eff)) obtained by Rayleigh/Compton (R/C) ratio and evaluated for the purpose of radiation shielding which contains boron compounds, which are commonly used as shield materials. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Effective atomic number (Z(eff)); Boron compounds; Shielding materials; Rayleigh/Compton scattering ratio; MASS ATTENUATION COEFFICIENTS; COMPTON-SCATTERING; RAYLEIGH; GLASSES; RATIO; Instruments & Instrumentation; Nuclear Science & Technology; Physics